Tindak Lanjut Hasil Rekomendasi Pemeriksaan Sebagai Penunjang Kualitas Laporan Keuangan Pemerintah Daerah - Andy Chandra Pramana; Meme Rukmini; Duwi Riningsih; Oktaviana Wahyu Prihardina; Mayciella So (JAF (Journal of Accounting and Finance), 2023)
The research was conducted to obtain empirical evidence related to the effect of Follow-up Examination Recommendation Results on the Quality of Local Government Financial Statements. The Regional Government of Nganjuk Regency which has received WTP opinions from BPK 5 times in a row so it is interesting to conduct research here whether the success cannot be separated from the Follow-up Results of Examination Recommendations from BPK. Follow-up of the Examination Recommendation Results are derived to 4 indicators, namely specific policies related to follow-up, other parties' responses, leadership commitment and leadership motivation, then tested for their influence with multiple linear regression analysis. As a result, these 4 indicators have an influence on the quality of local government financial statements. This research can be developed on other entities that have higher achievements, such as WTP opinions from BPK consecutively for 10 times, so that they can be used as a reference by other entities in maintaining and improving the quality of their financial statements. Keywords : follow-up recommendations on examination results; quality; local government financial statements